An analysis of a peri-urban sanitation market and farmers’ perception on excreta reuse in agriculture in Dangme West District, Ghana - Nimoh, Fred (2016)
A thesis submitted to The School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana, in fulfillment of the requirements for the degree of Doctor of Philosophy Department of Agricultural Economics, 2016